The Impact of IoT (Internet of Things) on Green Operations and Digitalization as a Business Strategy for Two Hotels in Palangkaraya - Lundjo, Gilbert Aurelio; Dr. Suwarno, S.Si., M.M., M.Si., CDMS, Dr. Suwarno, S.Si., M.M., M.Si., CDMS (International Economic Conference of Business and Accounting, 2025)
The integration of Internet of Things (IoT) technology and green principles offers promising prospects for the tourism industry in terms of improving destination quality and operational efficiency. IoT provides innovative solutions in tourism management, including the application of digital technology in the hospitality sector. Through a network of interconnected sensors and communication systems, IoT enables comprehensive data collection, real-time monitoring, and management of various operational aspects. Modern hotels are increasingly adopting digital solutions thanks to technological advancements to enhance their operational efficiency. Through case study analysis of several hotels to assess the use of digital-based management systems, the integration of online reservation platforms, and the use of technology across various operational areas of the hotel, it is evident that digital transformation can significantly enhance productivity, guest services, and customer satisfaction. This research also examines findings related to the impact of employee behavior on consumer service performance. Effective hotel operations require data privacy and security guarantees, resolution of technology compatibility issues, and substantial investments supported by environmentally conscious management (green operations). The implementation of green operations has proven to have a significant and positive impact on environmental performance. The study concludes that the full implementation of internal green management acts as a mediator between stakeholder pressure and environmental performance outcomes. Although the integration of IoT and green effects faces challenges, their potential benefits in developing Palangka Raya City as a tourist destination make it a highly promising strategy for future progress.